Pervaporation Process with PDMS/PVDF Hollow Fiber Composite Membrane to Recycle Phenol from Coal Chemical Wastewater - Jie, Yao; Dandan, Zhang; Shuren, Yang; Hong, You; Ziwei, Du; Biaoming, Li; Zhou, Yang; Zhongwei, Wang; Agtmaal, Sjack van; Chunhui, Feng; Bangjun, Han (Journal of Membrane and Separation Technology, 2013)
<!-- [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> To treat coal gasification wastewater containing phenol, polydimethylsiloxane (PDMS)/polyvinylidene fluoride (PVDF) hollow fiber composite membrane was made by dynamic negative pressure coating method, using PVDF hollow fiber membrane as base membrane, PDMS as modifying membrane material, to improve pervaporation performance of PDMS by the cross-linking modification. The influence of cross-linking agent, PDMS concentration, coating time on pervaporation performance of the composite membrane was investigated. Actual coal chemical wastewater with phenol concentration 1600-1800 mg/L, COD 13000-15000 mg/L was treated by the obtained PDMS/PVDF composite membrane, and at temperature 70℃, the flow rate of 10 L/h, pressure under membrane 3KPa, phenol flux 16.81 g/(m2·h), separation factor reaches 8.103. <!--[endif] -->